FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT SYNDROME PADA PERAWAT DI RSUD BAHTERAMAS, SULAWESI TENGGARA - Sujanah, Wiwin; Pratiwi, Arum Dian; Akifah, Akifah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Working as a nurse has the demands of heavy work in nursing care so that easy to experience fatigue can lead to burnout syndrome. Burnout syndrome is the occurrence of emotional fatigue, depressiveization, and decreased achievement of personal achievement due to stress that is often experienced by a worker and lasts a long time that causes negative attitudes towards a person. This study aims to find out the factors related to burnout syndrome in nurses in the Inpatient Installation of Bahteramas Hospital in Southeast Sulawesi Province. This type of research is observational analytics with a Cross Sectional Study approach. The population in this study was inpatient room nurses with a sample of 147 nurses selected with random sampling techniques. Data collection using maslach burnout inventory questionnaire, then analyzed using chi-square test. The results of this study showed that bound variables are associated with workloads with (p-value=0.000), dual roles (p-value=0.004), personality types (p-value =0.000) and there is no relationship between leadership style variables with burnout syndrome (p-value=0.164). The conclusion of this study is that there is a relationship between workload, dual role, and personality type with burnout syndrome, while the leadership style has no relationship with burnout syndrome in nurses in the Inpatient Installation of Bahteramas Hospital in Southeast Sulawesi Province. It is expected that the hospital needs to share the workload in accordance with the duties of nurses and the importance of nurses themselves make efforts to manage stress so that nurses can work well and can provide optimal services.